THE ROLE AND IMPORTANCE OF INFORMATION TECHNOLOGIES IN THE DEVELOPMENT OF LOGICAL THINKING OF PRESCHOOL CHILDREN - Oripova Nodima Khalilovna; Umurkulova Mastura Rakhmatullaevna (Web of Journals Publishing, 2024)
This article examines the crucial role of information technology in enhancing the effectiveness of preschool education. It discusses the evolving demands placed on educators in the digital age and highlights the significant benefits of incorporating information and communication technologies (ICT) in early childhood learning. The article outlines the expected outcomes of utilizing these technologies, including improved engagement, individualized learning experiences, and enhanced educational resources, ultimately contributing to better developmental results for preschool-aged children.
Keywords: preschool education, upbringing, innovation, professional skills, advanced pedagogical technologies, information communication technologies, presentation, animation, music, video, cartoon.